2016
DOI: 10.1210/jc.2015-3566
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Deficit in Obese Type 2 Diabetes, a Minor Role of β-Cell Dedifferentiation and Degranulation

Abstract: Therefore, although we concur that in type 2 diabetes there are endocrine cells with altered cell identity, this process does not account for the deficit in β-cells in type 2 diabetes but may reflect, in part, attempted β-cell regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
103
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 32 publications
11
103
1
3
Order By: Relevance
“…While increased β cell apoptosis may be responsible for the majority of decreased β cell mass in advanced T2DM patients (42,43), recently it has been suggested that an additional mechanism may exist. Thus, accumulation of dedifferentiated/ immature β cells, which express markers of both α and β cells, has been reported in mouse models of diabetes as well as in human T2DM islets (4,32,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While increased β cell apoptosis may be responsible for the majority of decreased β cell mass in advanced T2DM patients (42,43), recently it has been suggested that an additional mechanism may exist. Thus, accumulation of dedifferentiated/ immature β cells, which express markers of both α and β cells, has been reported in mouse models of diabetes as well as in human T2DM islets (4,32,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…While increased β cell apoptosis may be responsible for the majority of decreased β cell mass in advanced T2DM patients (42,43), recently it has been suggested that an additional mechanism may exist. Thus, accumulation of dedifferentiated/ immature β cells, which express markers of both α and β cells, has been reported in mouse models of diabetes as well as in human T2DM islets (4,32,(43)(44)(45). While the origin of these dedifferentiated/immature β cells is still controversial in humans (32,43), it is plausible that strategies to suppress β cell apoptosis and/or increase β cell differentiation/maturation would be effective at improving β cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPY also marks a highly proliferative insulin -cell-type derived from β cells that contributes to compensatory β cell expansion upon partial pancreatectomy (34). Impairment of β cell maturity contributes to β cell dysfunction in diabetes (17,18,35). Increased NPY in β cells upon diet-induced expansion and preceding diabetes onset in the rodent models suggests that cellular stress rather Regions marked with dotted line show pancreatic ganglia, which also express NPY.…”
Section: Discussionmentioning
confidence: 99%
“…BCM is regulated by the balance of newly formed betacells and beta-cell loss. Beta-cell replication and neogenesis are considered to be sources of newlyformed beta-cells, while beta-cell apoptosis is considered a major cause of beta-cell loss [2,49]. A recent rodent study has suggested beta-cell dedifferentiation to be another mechanism of beta-cell loss in diabetes [50].…”
Section: Ink4amentioning
confidence: 99%